2021
DOI: 10.21203/rs.3.rs-1058712/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introduction to the native plant species with phytoremediation potential growing in a high Fe and Zn contaminated site in the copper mine of Dehmadan, Iran

Abstract: Mining activity is one main source of heavy metal pollution. In this study, Al, Ba, Be, Ca, Cd, Co, Ce, Cr, Cu, Fe, Ga, Gd, K, La, Li, Mg, Mn, Na, Nb, Nd, Ni, P, Pb, S, Sc, Si, Sr, Ti, V, Y, Zn and Zr were measured by ICP-OES analyzing of the soils taken in the Dehmadan mining area, Chaharmahal and Bakhtiari, Iran. Al, Fe, Cu, Si and Zn were the most frequent metals in the mining area. Phytoremediation is one of the eco-friendly methods to effectively remediate soils contaminated with heavy metals. Consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Cd and Pb were found to be higher than the permissible limit values in the Ziziphora persica plant (Alinia-Ahandani et al, 2021). Cd, Pb, and Cr were found to be <0.05 mg kg -1 in the Ziziphora tenuior plant (Hajihashemi et al, 2021). When all species were considered together, it was observed that the most iron, chromium, and cadmium accumulated in the roots, arsenic was distributed in the leaves, and lead was distributed in all plant organs in similar proportions.…”
Section: Discussionmentioning
confidence: 87%
“…Cd and Pb were found to be higher than the permissible limit values in the Ziziphora persica plant (Alinia-Ahandani et al, 2021). Cd, Pb, and Cr were found to be <0.05 mg kg -1 in the Ziziphora tenuior plant (Hajihashemi et al, 2021). When all species were considered together, it was observed that the most iron, chromium, and cadmium accumulated in the roots, arsenic was distributed in the leaves, and lead was distributed in all plant organs in similar proportions.…”
Section: Discussionmentioning
confidence: 87%